Morphology development of immiscible polymer blends during melting in single-screw extruders : effect of composition and compatibilization - Cunha, S. M. (2011)
Melting in single screw extruders began to be studied in the fifties, based on the pioneering work of Maddock. Most theoretical and experimental studies used homopolymers as model systems. However, in practice, there has been a considerable evolution in terms of the complexity of the materials being extruded. In the case of polymer blends, the morphology developed during melting should determine the final blend properties. Therefore, this work aims at investigating the morphology evolution during the melting stage of immiscible physical and chemically compatibilized PA6/PP blends. In general, the sequence of steps of morphology evolution reported for twin screw extruders and batch mixers was observed, though adapted to the flow kinematics along a helical single screw channel. The global morphological development is not affected by blend composition, but distinct domains seem to be formed when in situ reactive compatibilization takes place.